DIMENSI BIMBINGAN ISLAM DALAM MANAJEMEN ILAHIYAH - Akbar, Nadzmi (UIN Antasari Banjarmasin, 2017)
In an increasingly complex era today, Islamic guidance and counseling services can be regarded as a necessity for every individual. But not all individuals receive Islamic guidance and counseling services, due to limited manpower, time and funds. In Islam guidance must be a shared responsibility, to achieve the happiness of the world and the hereafter. Islamic guidance can be implemented wherever and whenever, provided there is willingness and ability. Implementation of Divine Management in Government agencies is actually an effort to guide the employees to in the activities of life in the world always in the way of Allah SWT. Implementation of this divine management must be from the will and ability of the leader. The dimension of Islamic guidance in the Divine Management is on the Divine Leadership of Islamic Counselors, Values of Guidance in Pesantren Prostration, Guidance through Prophet Assembly of Science and Salary, Pilgrimage Pilgrimage as Media of Islamic Guidance, Pilgrimage of Grave as the media of Islamic Guidance.